A (re)construção do ethos discursivo do presidente Jair Bolsonaro no Twitter. - Rute Ferreira Fraga (2022)
The conservative populist discourse has being gaining ever more ground in the present global context, as it is shown, in Brazil, by the election of Jair Bolsonaro that took place in 2018. Taking this into account, the present thesis, based apon the French Discourse Analysis School, has as it’s main goal undertake an investigation over Jair Bolsonaro's ethos as it has being manifested through his official Tweeter account. Although claiming his oposition to traditional politics, and proclaiming himself to be an outsider regarding to the political scene, Jair Bolsonaro has started his career in it over 30 years ago. What strikes our attention - and ultimately has inspired this research - is his utilization of social media as one of his main means of communication, specially Tweeter. Given those considerations, we have sought to investigate the ethos (or ethe) which transpire from his tweets in trhee specific momento of his life in politics: as a Congressman (2017), as a Nominee (2018), and as president (2019). From a methodollogical point of view, considering that a great deal of his posts have do to with identitary issues, we have focused our attention on social minorities. As such, we have selected selected 5 posts from each stage of his career described above, tottaling 15 of them. Regarding the theorical foundation connected with the retoric of ethos, we have taken as a point of departure the premisses of Dominique Maingueneau, Patrick Charadeau and Ruth Amossy. Subsequentely, we have sought to mobilize some aspects of the Global Semantics Theory proposed by Maingueneau as an analytic device, those being: themes, intertextuality, vocabulary, enunciatory dexis, and, above all, the enunciation modus, which, focusing on the tone of a discourse, allow us to verify with greater clarity the ethos' mutatuons constructed in his tweets by the enunciator/Bolsonaro. As a result, we have found that an attempt has being made by the enunciator of deconstructing his previous ethos - which have being connected, as a rule, to bigoted attitudes and affirmations - so as to construct a new ethos, ambiguity being one of the main linguistical-discoursive strategies utilized by him. We also have found that, already by the time off his presidential campaing (2018), there is a change of "tone", which becomes more restrained in regard to discourses regarding native communities, Black population, migrants/refugees and women. Despite of that, concerning his remarks towards the LGBTQIAP+ community, the enounciator keeps hos aggressive "tone" trhough all of the stages analyzed. In conclusion, despite the attempt emprehended by Bolsonaro to (re)construct his portrait (ethos), the tweets analyzed pointed to the prevalence of his previous ethos in regard to social minorities, even if it has assumed a more restrained "tone" one time or another.